The diagnostic value of Gram stain for initial identification of the etiologic agent of peritonitis in CAPD patients - Bezerra, Dinoráh A. [UNESP]; Silva, Mario B. [UNESP]; Caramori, Jaqueline S.T. [UNESP]; Sugizaki, Maria F.; Sadatsune, Teruê; Montelli, Augusto C.; Barretti, Pasqual [UNESP] (My University, 1997)
Objective: To evaluate the effectiveness of the Gram stain in the initial diagnosis of the etiologic agent of peritonitis in continuous ambulatory peritoneal dialysis (CAPD). Design: Retrospective study analyzing the sensitivity (S), specificity (SS), positive predictive value (+PV), and negative predictive value (-PV) of the Gram stain relating to the results of cultures in 149 episodes of peritonitis in CAPD. The data were analyzed in two studies. In the first, only the cases with detection of a single agent by Gram stain were taken (Study 1). In the second, only the cases with two agents in Gram stain were evaluated (Study 2). Setting: Dialysis Unit and Laboratory of Microbiology of a tertiary medical center. Patients: Sixty-three patients on regular CAPD who presented one or more episodes of peritonitis from May 1992 to May 1995. Results: The positivity of Gram stain was 93.2% and the sensitivity was 95.7%. The values of S, SS, +PV, and -PV were respectively: 94.9%, 53.5%, 68.3%, and 90.9% for gram-positive cocci and 83.3%, 98.8%, 95.2%, and 95.6% for gram-negative bacilli. The association of gram-positive cocci plus gram-negative bacilli were predictive of growth of both in 6.8%, growth of gram-positive cocci in 13.7%, and growth of gram-negative bacilli in 72.5%. Conclusions: The Gram stain is a method of great value in the initial diagnosis of the etiologic agent of peritonitis in CAPD, especially for gram-negative bacilli.
Keywords: Gram stain; Peritonitis; bacterial growth; bacterial peritonitis; bacterium culture; continuous ambulatory peritoneal dialysis; diagnostic accuracy; diagnostic value; gram negative bacterium; gram positive bacterium; gram staining; human; major clinical study; nonhuman; priority journal; retrospective study; Evaluation Studies; Gentian Violet; Gram-Negative Bacterial Infections; Gram-Positive Bacterial Infections; Humans; Peritoneal Dialysis, Continuous Ambulatory; Phenazines; Retrospective Studies; Sensitivity and Specificity; Staining and Labeling